Novel Preosteoclast Populations in Obesity-Associated Periodontal Disease. (March 2022) - Kwack, K.H.; Zhang, L.; Sohn, J.; Maglaras, V.; Thiyagarajan, R.; Kirkwood, K.L.
Although there is a clear relationship between the degree of obesity and periodontal disease incidence, the mechanisms that underpin the links between these conditions are not completely understood. Understanding that myeloid-derived suppressor cells (MDSCs) are expanded during obesity and operate in a context-defined manner, we addressed the potential role of MDSCs to contribute toward obesity-associated periodontal disease. Flow cytometry revealed that in the spleen of mice fed a high-fat diet (HFD), expansion in monocytic MDSCs (M-MDSCs) significantly increased when compared with mice fed a low-fat diet (LFD). In the osteoclast differentiation assay, M-MDSCs isolated from the bone marrow of HFD-fed mice showed a larger number and area of osteoclasts with a greater number of nuclei. In the M-MDSCs of HFD-fed mice, several osteoclast-related genes were significantly elevated when compared with LFD-fed mice according to a focused transcriptomic platform. In experimental periodontitis, the number and percentage of M-MDSCs were greater, with a significantly larger increase in HFD-fed mice versus LFD-fed mice. In the spleen, the percentage of M-MDSCs was significantly higher in HFD-fed periodontitis-induced (PI) mice than in LFD-PI mice. Alveolar bone volume fraction was significantly reduced in experimental periodontitis and was further decreased in HFD-PI mice as compared with LFD-PI mice. The inflammation score was significantly higher in HFD-PI mice versus LFD-PI mice, with a concomitant increase in TRAP staining for osteoclast number and area in HFD-PI mice over LFD-PI mice. These data support the concept that M-MDSC expansion during obesity to become osteoclasts during periodontitis is related to increased alveolar bone destruction, providing a more detailed mechanistic appreciation of the interconnection between obesity and periodontitis.